2009
DOI: 10.1073/pnas.0801032106
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the TRAP–Anti-TRAP complex

Abstract: Tryptophan biosynthesis is subject to exquisite control in species of Bacillus and has become one of the best-studied model systems in gene regulation. The protein TRAP (trp RNA-binding attenuation protein) predominantly forms a ring-shaped 11-mer, which binds cognate RNA in the presence of tryptophan to suppress expression of the trp operon. TRAP is itself regulated by the protein Anti-TRAP, which binds to TRAP and prevents RNA binding. To date, the nature of this interaction has proved elusive. Here, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
73
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 28 publications
3
73
0
Order By: Relevance
“…It is also interesting to note the conditions that lead to crystal formation of both the AT 12 (21,38) and the AT 3 -TRAP complex (27) are consistent with the pHdependent oligomerization reported in this paper. Bsu AT 12 was crystallized from a pH 6.5 solution (21) where N-terminal protonation would favor formation of the dodecameric form, whereas the AT 3 -TRAP complex was crystallized at a pH of 8.5 (27) where trimer dominates. The present measurements permit a rough analysis of the oligomeric state of AT in bacterial cells.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…It is also interesting to note the conditions that lead to crystal formation of both the AT 12 (21,38) and the AT 3 -TRAP complex (27) are consistent with the pHdependent oligomerization reported in this paper. Bsu AT 12 was crystallized from a pH 6.5 solution (21) where N-terminal protonation would favor formation of the dodecameric form, whereas the AT 3 -TRAP complex was crystallized at a pH of 8.5 (27) where trimer dominates. The present measurements permit a rough analysis of the oligomeric state of AT in bacterial cells.…”
Section: Discussionsupporting
confidence: 73%
“…Alanine scanning studies of AT highlighted residues important for TRAP binding and showed that dodecameric AT was unlikely to be able to bind to TRAP (26). In agreement with these findings, crystallographic studies of 12-mer-forming variants of TRAP in complex with AT showed six AT trimers (AT 3 ) arranged along the outside of the TRAP ring, suggesting that the trimer is the species that binds to TRAP (27). However, in vivo studies of the relative concentrations of ATand TRAP seem to show that TRAP activity can be fully inhibited by AT present at a ratio of two AT 3 per TRAP ring (28).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Depending on how many TRAP molecules per cell are Trp activated and AT free, TRAP will be partially or fully active. Thus, TRAP can bind up to 11 molecules of Trp, to some extent cooperatively (4,25,36,43), and each bound Trp molecule can contribute to TRAP's RNA-binding ability. However, even when TRAP is fully activated, AT can bind to TRAP and block TRAP's RNAbinding ability.…”
Section: Discussionmentioning
confidence: 99%
“…When free Trp is plentiful and available, it binds to-and activates-TRAP. The TRAP protein contains 11 identical protein subunits, 11 Trp binding sites, and 11 Lys-Lys-Arg motifs on the periphery of the protein complexto Trp-activated TRAP at its RNA-binding surface (35,36,43) and preventing TRAP from binding to its target RNAs. Thus, by binding to TRAP, AT can regulate transcription or translation of all the operons regulated by TRAP (39,40).…”
mentioning
confidence: 99%